Methodology for Multidimensional, Systemic and Transdisciplinary Analysis in Agricultural Research - Domínguez-Hernández, Martha Elena; Zepeda-Bautista, Rosalba (Transdisciplinary journal of engineering & science, 2025)
Agricultural production is a complex and dinamic system. It is affected by environmental, political, social, cultural, economic, and technological factors. The problems related to agroecosystems must be studied from a multidimensional perspective that guarantees obtaining solutions applicable to local conditions. Some existing methodologies offer tools that allow analysis to be obtained, they do not provide a framework that considers minimum requirements for the design of interventions. Based on the results obtained in the agricultural research and the work carried out with farmers, a comprehensive analysis was made and a multidimensional methodology with a systemic and transdisciplinary approach that allows analyzing and evaluating is proposed agroecosystems, and measure the effect of interventions designed to improve them. The methodology has 11 phases that include the definition of the object of study, the diagnosis of the current situation, the design and application of interventions to the analysis of experimental results and presentation of results.